Mindset And Mental Toughness Of Basketball Athletes Under 18 Years Old - Foekh, Risto Gerol; Priambodo, Anung (UNIVERSITAS NEGERI MAKASSAR, 2025)
Mindset and mental toughness are two crucial factors that affect the performance of basketball athletes under the age of 18. A positive mindset, such as a growth mindset, encourages young athletes to continue learning, overcome failures, and improve their skills. Meanwhile, mental toughness allows them to stay focused, manage pressure, and face challenges and failures with high resilience. The purpose of this study is to discuss the concept of mindset and mental toughness in the context of basketball athletes under 18 years old. This discussion will also explain how these two elements affect the performance of young athletes and how coaches and the environment can play a role in the development of both. This study uses a qualitative approach with a conceptual study design. This type of research aims to understand the phenomenon that occurs through a deep understanding of the experiences and perspectives of young basketball athletes in developing a mindset and mental toughness. This approach focuses more on descriptive data collection and text analysis or in-depth interviews than quantitative measurement. Mindset and mental toughness are two psychological elements that greatly affect the performance of basketball athletes under the age of 18. Having a positive mindset (growth mindset) and tested mental toughness can help young athletes overcome various obstacles and pressures, both in training and matches. Therefore, coaches, families, and the surrounding environment need to provide positive support and appropriate coaching to develop both aspects. That way, young athletes not only develop in technical aspects but also in mental readiness to face even greater sporting challenges in the future.